Kult Ojca w Duchu i prawdzie (J 4, 23) - Kudasiewicz, Józef (The Biblical Annals, 2017)
The author sets out to interpret the widely disputed and controversial text of the fourth Gospel, 4. 23. He rejects those interpretations taking the word "spirit" in the Greek, abstract and Platonizing sense, i. e. as 'in a spiritual way', meant as a contrast to what is bodily and material. He also rejects the psychologizing interpretation, 'inwardly'. Nor does he accept the reading of the word "truth" as 'truly' or 'genuinely'. The two expressions must be read in the Biblical, and more specifically the Johannine sense. "Spirit" denotes the Holy Spirit, and "truth" denotes God’s revelation and the person of Jesus, who is its climax. The New Testament worship is the worship of the Father in the truth reveded by Jesus Christ (and in Christ the Truth); it also has a pneumatological dimension: "in spirit", i. e. under the influence and inspiration of the Spirit.